Reconstruction After En Bloc Resection of a Distal Radius Tumor. An Updated and Concise Review - Chobpenthai T; Poosiripinyo T; Warakul C (Orthopedic Research and Reviews, 2023)
Thanapon Chobpenthai,1 Thanate Poosiripinyo,2 Chawin Warakul1 1Princess Srisavangavadhana College of Medicine, Chulabhorn Royal Academy, Bangkok, Thailand; 2Department of Orthopaedics, Khon Kaen Hospital, Khon Kaen, ThailandCorrespondence: Thanapon Chobpenthai, Princess Srisavangavadhana College of Medicine, Chulabhorn Royal Academy, 906 Kamphaengphet 6 Road, Talat Bang Khen, Lak Si, Bangkok, 10210, Thailand, Tel +662-576-6000, Fax +662-576-6904, Email thanapon.cho@cra.ac.thAbstract: The distal radius is rarely affected by either primary or metastatic bone cancers. The most frequent tumors of the distal radius are giant cell tumors, which are benign tumors with the propensity to invade. En bloc excision of giant cell tumors of the distal radius achieves a low recurrence rate but compromises the wrist joint, necessitates a significant reconstruction, and has functional consequences. Reconstruction after en bloc resection of a distal radius bone tumor is challenging. Furthermore, orthopedic oncologists disagree on treating such long bone anomalies most effectively. The present article summarizes the various biological and non-biological reconstruction techniques performed after en bloc resection of a distal radius tumor, discusses the advantages and disadvantages of each reconstruction strategy, and summarizes several case studies and case reports.Keywords: benign bone tumor, giant cell tumor, en bloc resection, reconstruction technique, distal radius tumor